EUFOREA summit in Brussels 2023: inspiring the future of allergy & respiratory care - Hellings, P. W.; Lau, S.; Scadding, G. K.; Bjermer, L.; Backer, V.; Chaker, A. M.; Conti, D. M.; De Corso, E.; Diamant, Z.; Djukanovic, R.; Fokkens, W.; Gevaert, P.; et al. (Frontiers in Allergy, 2023)
In March 2023, the European Forum for Research and Education in Allergy and Airways diseases (EUFOREA) organized its bi-annual Summit in Brussels with expert panel members of EUFOREA, representatives of the EUFOREA patient advisory board, and the EUFOREA board and management teams. Its aim was to define the research, educational and advocacy initiatives to be developed by EUFOREA over the next 2 years until the 10 th anniversary in 2025. EUFOREA is an international non-for-profit organization forming an alliance of all stakeholders dedicated to reducing the prevalence and burden of chronic allergic and respiratory diseases via research, education, and advocacy.